(untitled) (Contemporary Journal of Social Science Review, 2025)
The present study aimed to investigate the relationship between perceived stress and psychological well-being among patients diagnosed with brain cancer in Pakistan. Brain cancer patients often face physical, emotional, and social challenges that contribute to elevated stress levels, which in turn may adversely affect their psychological well-being. A sample of 200 patients (both men and women), aged at 18 to 60, was selected from private and government hospitals across Pakistan using a purposive sampling technique. Standardized tools, including the Perceived Stress Scale (PSS) and the Psychological Well-Being Scale (PWB), were administered to measure stress and psychological wellbeing. Correlational analysis revealed a significant negative relationship between perceived stress and psychological wellbeing, indicating that higher levels of stress were associated with lower well-being. Furthermore, regression analysis confirmed that perceived stress significantly predicted psychological well-being, highlighting the detrimental impact of stress on mental health among brain cancer patients. These findings emphasize the urgent need for comprehensive psychosocial interventions, including stress management, counseling, and supportive care, to enhance the overall quality of life of patients coping with brain cancer.